Osteopontin as a molecular prognostic marker for melanoma - Javier Rangel; Mehdi Nosrati; Sima Torabian; Ladan Shaikh; Stanley P. L. Leong; Chris Haqq; James R. Miller; Richard W. Sagebiel; M. Kashani-Sabet (2007)
Abstract BACKGROUND. Osteopontin has been suggested as a marker of disease progression in patients with melanoma because of its overexpression in recent microarray analyses. However, its prognostic role in melanoma has not been fully defined. METHODS. Osteopontin expression status was examined using immunohistochemical analysis of a tissue microarray that contained primary cutaneous melanomas from 345 patients. The correlation between osteopontin expression and several histologic markers for melanoma was assessed by using the Chi‐square test and the Le directional test. The impact of osteopontin expression on recurrence‐free survival (RFS) and disease‐specific survival (DSS) of patients with melanoma was examined using Cox regression and Kaplan‐Meier analyses. The impact of increasing osteopontin expression on sentinel lymph node (SLN) metastasis was assessed using logistic regression analysis. RESULTS. High osteopontin expression was associated with increased tumor thickness ( P = .037), Clark level ( P = .035), and mitotic index ( P = .046). Kaplan‐Meier analysis demonstrated an association between osteopontin expression and reduced RFS ( P < .03) and DSS ( P = .05). Multivariate Cox regression analysis demonstrated that high osteopontin immunostaining had an independent impact on the DSS of this melanoma cohort ( P = .049). In addition, osteopontin expression was significantly predictive of SLN metastasis ( P = .009) and SLN burden, as assessed by the mean number of SLN metastases ( P = .0025). Multivariate logistic regression analysis demonstrated an independent role for osteopontin expression in predicting SLN status ( P = .0062). CONCLUSIONS. The current results validated the role of osteopontin as an independent prognostic marker for melanoma and provided new evidence for its predictive role in melanoma lymph node metastasis. Cancer 2008. © 2007 American Cancer Society.